2021
DOI: 10.1002/pits.22579
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐method analysis of the implementation process of universal screening in a tiered mental health system

Abstract: Schools are encouraged to take a proactive approach to mental health through the use of a tiered system of supports facilitated by universal mental health screening. However, schools may experience difficulty implementing universal screening and large‐scale systems change. The purpose of this study was to explore multilevel implementation determinants, identify strategies that aided implementation, and examine how implementation determinants and strategies impacted implementation reach for two schools adopting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The purpose of the present study was to begin establishing the consequential validity evidence base for universal SEB screening and inform future research practice that improves its utility such that the hopes of addressing the SEB risk of all students are realized. As evidenced in recent studies examining adoption (Burns & Rapee, 2021) and implementation (Brann et al, 2021) of universal SEB screening, using universal SEB screening results in schools is complex and fraught with organizational (e.g., access to data, availability of satisfactory interventions) and individual (e.g., perceptions of need, concern, and resource availability) challenges, especially when one third of the sample is identified with SEB risk as in the present study. Thus, research examining and informing its utility is critical for realizing its intended benefits and establishing its consequential validity.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The purpose of the present study was to begin establishing the consequential validity evidence base for universal SEB screening and inform future research practice that improves its utility such that the hopes of addressing the SEB risk of all students are realized. As evidenced in recent studies examining adoption (Burns & Rapee, 2021) and implementation (Brann et al, 2021) of universal SEB screening, using universal SEB screening results in schools is complex and fraught with organizational (e.g., access to data, availability of satisfactory interventions) and individual (e.g., perceptions of need, concern, and resource availability) challenges, especially when one third of the sample is identified with SEB risk as in the present study. Thus, research examining and informing its utility is critical for realizing its intended benefits and establishing its consequential validity.…”
Section: Discussionmentioning
confidence: 79%
“…The problem-solving teaming process in schools is most historically implemented with schools having individual student conversations (Rosenfield et al, 2018) but with one third of students being identified by the screener, schools need to learn to coordinate service delivery at the systems level also. Schools expressed similar areas for improvement in a recent mixed-methods case study of universal SEB screening implementation (Brann et al, 2021). Shifting conversations from individual student problem-solving to service delivery system coordination should also provide opportunities to frequently monitor and evaluate outcomes for continuous quality improvement (Splett & Maras, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This echoes the need for a multi-tiered system that includes universal supports for all students along with targeted and intensive interventions at Tier II and Tier III. Schools that have worked to develop school-based mental health MTSS have been successful in serving students' mental health needs and have also discovered implementation strategies that best promote successful and sustainable implementation of services across the MTSS, including universal mental health screening (Brann et al, 2019; Skaar, in press).…”
Section: Prepare To Act On Screening Datamentioning
confidence: 99%
“…Qualitative focus group data allows us to probe deeper into the nuance and rationalization for quantitative ratings (Palinkas et al, 2011; Regnault et al, 2018). Mixed methodology is a common approach in implementation research, particularly in the school context, and several studies have used mixed methods (Brann et al, 2021; Hemphill et al, 2015; McLaughlin et al, 2020).…”
mentioning
confidence: 99%